Distress influence in fibromyalgia - I. Saracco; C. Venditti; S. Stisi (PAGEPress Publications, 2011)
Objective: Fibromyalgia syndrome (FM) is a controversial chronic painful syndrome. Although the aetiology is unknown, FM is frequently correlated with stressors events. Recent studies highlighted the frequent comorbidity with anxiety and depression and a close relationship between stress and pain. Methods: We evaluated the relevance of stressors events in 23 patients with FM (mean age: 45.7±7.4 SD), compared with 18 healthy controls (mean age: 41.7±6.4 SD) and 17 patients with dysfunctional syndrome (mean age 40.8±6.1). We performed the italian validated rapid assessment of the stress test (VRS) for the assessment of stress. Furthermore, we evaluated the psychological history for a semi-quantitative assessment (IVAS) of the 49 stress-generating events listed in 1994's DSM-IV. Results: The group of "healthy" subjects showed stress values at VRS test (mean: 7.00±4.65 SD) significantly lower (p=0.0001) than the patients with "dysfunctional syndrome" (mean 14.82±7.69 SD) and those with FM (mean 20.04±9.90 SD). The IVAS test, showed higher values in FM subgroup than healthy (p=0.0001) and dysfunctional syndromes (p=0,007). Also, the patients with FM showed a greater gravity to attribute to single stressors events (p=0.02). Conclusions: Our results emphasize the importance of the perceived stress among the patients with FM, and support the hypothesis that FM could be due to a psycho-neuro-endocrinal response to several stressors events in patients with genetical hyperresponsiveness to stress.